Faktor-Faktor yang Memengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor - Putra, Ade Dwika; Merkusiwati, Ni Ketut Lely Aryani (Jurnal Samudra Ekonomi dan Bisnis, 2025)
This research aims to obtain empirical evidence regarding the influence of taxpayer awareness, motor vehicle tax relief, the SAMSAT Drive Thru service system, along with SAMSAT Kerti on motor vehicle taxpayer compliance in Denpasar City. This research was carried out at the Regional Tax and Retribution Service UPTD Office, Bali Province, Denpasar City. This research uses the Theory of Planned Behavior along with Attribution Theory. The sample was determined using accidental sampling with a sample of 100 respondents calculated using the Slovin formula. Data were collected through questionnaires, and data were analyzed using multiple linear regression methods. Findings show that taxpayer awareness, motor vehicle tax relief, the SAMSAT Drive Thru service system, and SAMSAT Kerti, have a positive effect on motor vehicle taxpayer compliance in Denpasar City.